Catalytic Ring Expansion Adventures - Njardarson, Jon T. (Synlett, 2013)
This account summarizes the Njardarson group ring expansion journey from early vinyl oxirane explorations to the latest vinyl oxetane ring expansion discoveries. The evolution of the program and incredible success of Cu(hfacac)2 as catalyst is detailed. Application of these new ring expansion reactions to natural product, pharmaceutical and commodity chemical targets is discussed as well as our intriguing mechanistic journey and interesting entry into the world of chiral counterion catalysis.
Keywords: ring expansion; catalysis; strained rings; thiiranes; aziridines; oxiranes; oxetanes